The Role of Alkali Cations on the Selectivity of 5-Hydroxymethylfurfural Electroreduction on Glassy Carbon - Asfia, Mohammad Peirow; Cuomo, Angelina; Kloth, Ricarda; Mayrhofer, Karl J.J.; Nikolaienko, Pavlo (Chemsuschem, 2024)
In the past decade, organic electrosynthesis has emerged as an atom- and energy-efficient strategy for harvesting renewable electricity that provides exceptional control over the reaction parameters. A profound and fundamental understanding of electrochemical interfaces becomes imperative to advance the knowledge-based development of electrochemical processes. The major strategy toward an efficient electrochemical system is based on the advancement in material science for electrocatalysis. Studies on the complex interplay among electrode surface, electrolyte, and transformation intermediates have only recently started to emerge. It involves acquiring atomic-scale insights into the electrochemical double layer, for which the identity and concentration of composing ions play a crucial role. In this study, we present how the identity and concentration of alkali cations impact the selectivity of aldehyde functionality electroreduction. As a case-study transformation, we set the electrochemical conversion of 5-hydroxymethylfurfural (HMF), a promising biomass-derived feedstock for the sustainable production of polymer or fuel precursors. Our findings reveal a consistent trend of the selectivity shift towards 2,5-bis(hydroxymethyl)furan (BHMF) as a function of cation size and concentration, rationalized by specific cation adsorption at the glassy carbon (GC), followed by the increase in the electrode surface charge density.
CRIS-Team Scopus Importer:2024-06-14
Keywords: 5-Hydroxymethylfurfural; Alkali cation; Electrochemical interface; Mass spectrometry; Time-resolved product analysis